Meningococcal septicemia in a young immunocompetent girl - Muco, Ermira; Karruli, Arta; Kraja, Dhimiter (Acta Medica, 2023)
Meningococcal septicemia is a bloodstream infection caused by Neisseria meningitis. Clinical manifestations vary, from mild disease to severe meningococcaemia which may present first with high fever, severe myalgia, headache, skin and mucosal petechiae and can progress rapidly to septic shock with multi-organ dysfunction syndrome (MODS). Case presentation: A 17-year-old immunocompetent girl was admitted to the Infectious Disease ward, Mother Theresa University Hospital with a 3-4-days history of headache, vomiting, diarrhea, fever, cough, arthralgia. She had hypotension, tachypnea, tachycardia, pharyngeal erythema and generalized ecchymotic spots. She was transferred immediately to the Intensive Care Unit. Laboratory findings showed decrease of hemoglobin, platelet count, albumin; increase of AST, ALT, LDH, CPK. Neisseria meningitidis was cultured from cerebrospinal fluid. Latex agglutination test resulted positive for N. meningitidis Gr B. She was immediately treated with Ceftriaxone, hydrocortisone, i.v. fluids, albumin, dopamine/dobutamine, fresh frozen plasma, platelet mass, bicarbonate, cryoprecipitate. The meningococcal rash began to spread rapidly taking on the appearance of ecchymotic lesions. Her clinical condition worsened rapidly and was placed under mechanical ventilation and died within 31 hours of admission to the hospital as a result of septic shock. Conclusions: Young patients presenting with fever, severe myalgia, headache, skin and mucosal petechiae must be tested for Neisseria meningitis. This infection is a medical emergency that requires rapid diagnosis, immediate antimicrobial therapy and intensive care support as it may be deadly in a matter of hours. People including health workers who have been in prolonged and close contact with the patient should receive antibiotic prophylaxis.